Inovasi Pembelajaran Membaca Al-Qur’an Berbasis Game Edukasi: Analisis Efektivitas Aplikasi Belajar Hijaiyah di Era Digital - Alam Tarlam; Kemuning Khansa Mahdiyyah; Sekar Catur Wulandari (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study discusses innovations in Qur’an reading instruction through the use of an educational game, specifically by analyzing the effectiveness of the Belajar Hijaiyah application in the digital era. The background of this research stems from the need to modernize Qur’anic learning media, especially for young children who are generally more attracted to interactive, technology-based platforms. This study employs a qualitative descriptive method, with data collected through application feature observation, content analysis, and a review of user feedback on the Play Store. The findings indicate that Belajar Hijaiyah offers several interactive features such as pronunciation audio, quiz games, and letter visualizations that enhance children’s motivation and interest in learning. In terms of usability, the application is considered easily accessible and user-friendly. However, the study also identifies several limitations, including certain features that are only available through subscription. Overall, the Belajar Hijaiyah application is effective as a supplementary medium for teaching Qur’an reading, particularly in the introductory stage of learning Hijaiyah letters. This research contributes to the development of digital-based Islamic educational media and encourages the integration of technology into Qur’anic instruction.